PENGARUH PEMBERIAN PAKAN TAMBAHAN CACING SUTRA TERHADAP PERTUMBUHAN IKAN GABUS (Channa striata) - Wulandari, Cessi; Ruyani, Aceng; Singkam, Abdul Rahman; Kasrina, Kasrina; Husein, Ahmad Saddam (Jurnal Teknologi Perikanan dan Kelautan, 2024)
The snakehead (C. striata) is a freshwater fish species that inhabits swampy areas and rivers. It has high economic value, with its selling price determined per centimeter of its body length and is very useful in the medical and industrial sectors. Snakehead fish has good nutritional content, especially albumin. The growth of snakehead fryis largely determined by the quality of feed provided. This study aims to analyze the growth rate of snakehead fry by providing additional feed in the form of Tubifex sp. The experiment utilized four plastic aquariums measuring 40 x 30 x 30 cm, calipers, digital scales, a dissolved oxygen (DO) meter, a total dissolved solids (TDS) meter, and a pH meter. The materials used in the experiment included freshwater, fish pellets (PF 1000) produced by Prima Feed, snakehead fish, and silkworms. The research method used a Completely Randomized Design (CRD) with four treatments: P1 (100% pellets), P2 (75% pellets + 25% silkworms), P3 (50% pellets + 50% silkworms), and P4 (25% pellets + 75% silk worms). Results indicated that the addition of silkworms significantly affected in the growth in weight, length, and width of snakehead fry. The best growth was observed in treatment P4 (25% pellets + 75% silk worms), with an average absolute length of 24.31±9.89 mm, an average absolute width of 3.41±1.66 mm, and an average absolute weight of 18.28±6.40 g.